194 The uclpartners proactive care frameworks – optimising cvd prevention post covid. innovation to restore and improve care in the high-risk conditions and prevent heart attacks and strokes at scale. (4th June 2021) - Kearney, Matt; Shah, Deep; Peate, Stephanie; Robson, John; Williams, Helen; Antoniou, Sotiris; Butt, Mandeep; Saleemi, Aiysha; Amevenu, Daphne; Hameed, Nausheen; Khanji, Mohammed; McErlean, Mairead; et al.
Abstract : Introduction: COVID-19 has disrupted pathways of care for over 12 months. Primary care has transformed dramatically with much care being provided remotely. The COVID surges and vaccination programme have reduced capacity further. People with conditions such as hypertension, cardiovascular disease and diabetes depend on regular review and treatment optimisation to keep them well. There is a high risk that continued disruption to proactive care will drive an increase in exacerbations and complications. It is likely this will drive further waves of demand for urgent care over the coming months in primary care, in emergency departments and in hospital admissions. Methods: The team of GPs & pharmacists at UCLPartners, with patient and public support, developed proactive care frameworks for six conditions including atrial fibrillation, hypertension, high cholesterol and type 2 diabetes mellitus. The frameworks focus on the 'how to' of delivering care in the new world of primary care post COVID-19. They are built on 4 principles: virtual where appropriate, use of the wider workforce, step change in self-management, and use of digital resources. For each condition, the frameworks include: risk stratification tools; pathways that support remote care and deploy staff such as healthcare assistants and social prescribers to systematically support education, self-management and lifestyle change; scripts, protocols and training to guide these staff in consultations; digital tools; and resources to support treatment optimisation. The frameworks include clinical and project management support for local pathway adaptation and implementation. Results: The frameworks have gained wide traction in primary care across England. There have been over 2, 700 downloads of the search/stratification tools with evidence of implementation in several regions. In the UCLP geography, North East London and North Central London have adopted the frameworks for roll out across 475 GP practices and 2.8 million people. NHSEngland has now adopted the Frameworks as a key part of the NHS@Home programme with plans to support at scale national roll out. Evaluation is being commissioned. Conclusions: The UCLPartners Proactive Care Frameworks provide systematic, evidence-based support to restore services post COVID: stratifying so that higher risk patients can be prioritised and workload managed; maximising remote care; optimising personalisation and support for self-care. By using a population health management approach together with comprehensive resources to support clinical management in real world primary care, the frameworks provide a platform not just to restore services but to optimise treatment and outcomes in the high-risk conditions for CVD. The widespread national traction the frameworks are gaining suggests that despite the pandemic, this brings an opportunity to deliver the NHS Long Term Plan ambitions for CVD prevention and prevent 150, 000 heart attacks, strokes and cases of dementia. Conflict of Interest: none